Earth materials in urban environments - toward building continuity with the past - Thomas, Katherine (School of Architecture, Planning and Geomatics, 2023)
This dissertation looks at redesigning urban infill to promote a decolonial and environmentally sensitive city that is connected to its history, people, and nature. The inquiry is sparked by experiments in making Compressed Earth Blocks, mud and straw bricks, and shell-crete, and explores the potential of building with locally sourced, earth-based materials in an urban context. Theoretical explorations focus on decoloniality and the relationship between materials and colonisation, natural systems and urban-nature divides, and appropriate technologies and their potential to empower community at the human scale. These theory and technology studies inform the design of an urban infill building in the East City in Cape Town. On the corner of Harrington and Albertus Street, the site is a recently demolished Victorian warehouse building that was destroyed in a fire in 2020. What remains on the site is a 1940's attachment to the original building, a narrow but deep concrete framed sliver of a warehouse. The design uses this structure as an armature to support a set of infill buildings that explore the benefit of narrow typologies in encouraging low rise density in cities. The architecture is made with lightweight timber and steel structures that help support multistorey earth walls. Concrete- and carbon-heavy architecture is questioned and juxtaposed with hybrid tectonics, taking lessons from history to design congruous urban futures.